ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PURCHASE INTENTION PADA PAKAIAN OLAHRAGA PREMIUM YANG MELAKUKAN USAHA WIRAUSAHA DI PLATFORM E COMMERCE - Rafly Aditya Mukti; Dewi Fatmasari; Sinta Petri Lestari (Jurnal Ilmiah Ekonomika & Sains, 2024)
This research aims to test and analyze the factors that influence purchase intention for premium sportswear that carries out online shopping entrepreneurship. The population in this study were all customers at premium sportswear PT A. The sample obtained was 100 respondents using purposive sampling. The research results show that consumer reviews have a positive effect on purchase intention. Product originality has a positive effect on purchase intention. User interface has a positive effect on purchase intention. Delivery has a positive effect on purchase intention. Customer reviews, product originality, user interface, and delivery have a positive influence on purchase intention.